Pertanggungjawaban Pidana Bank Sebagai Pengguna Artificial Intelligence - Frans, Mardian Putra; Sari, Agustina Indah Intan; Panji, Krismelia Y; Ismara, Yudhistira Buana Cipta (Universitas Semarang, 2024)
The purpose of the research is to study and analyze the issue of the use of artificial intelligence (AI) by banks that results in losses to customers. To respond to the issue, this paper argues that banks as AI users should be held criminally liable despite the lack of mens rea in banks as corporations which are legal entities. For this reason, this paper uses the identification theory as an analytical tool for bank criminal liability. The issue is compiled on the results of normative legal research with a statute approach and conceptual approach. The results of the study show that based on the identification theory, the bank as an AI user can be held criminally liable with the public prosecutor must identify the person who committed the criminal act (actus reus) is the management as the controlling personnel (directing mind or controlling mind). The location of the AI mens rea is in the approval of the corporate controller to use AI, meaning that the approval is interpreted as the inner attitude of the controller to accept the risks arising from the use of AI. Tujuan dari penelitian untuk menganalisis isu penggunaan artificial intelligence (AI) oleh bank yang berakibat pada kerugian bagi nasabah. Untuk menanggapi isu tersebut, tulisan ini berpendapat bahwa bank sebagai pengguna AI patut dimintai pertanggungjawaban pidana meskipun tidak mempunyai mens rea pada bank sebagai korporasi yang merupakan badan hukum. Untuk itu, tulisan ini menggunakan teori identifikasi sebagai pisau analisis terhadap pertanggungjawaban pidana bank. Isu tersebut disusun atas hasil penelitian hukum normatif dengan pendekatan undang-undang (statute approach) dan pendekatan konseptual (conceptual approach). Hasil penelitian menunjukan, berdasarkan teori identifikasi, bank sebagai pengguna AI dapat dimintai pertanggungjawaban pidana dengan penuntut umum harus mengidentifikasi yang melakuan perbuatan pidana (actus reus) adalah pengurus sebagai personil pengendali (directing mind atau controlling mind). Letak mens rea AI ada pada persetujuan pengendali korporasi menggunakan AI, artinya sikao persetujuan tersebit dimaknai sebagai sikap batin pengali untuk menerima resiko yang timbul akibat penggunaai AI.